Teaching English to Visually-Impaired Students: An Analysis of Teacher’s Problems - Lenny Marzulina; Dian Erlina; Muhamad Holandiyah; Kasinyo Harto; Herizal Herizal; Rizqy Dwi Amrina; Nopalia Nopalia (Edukasi, 2021)
The aim of this study was to find out the teachers’ problems in teaching English to visually-impaired students. The participants of the study were two English teachers at one special school in Palembang, Indonesia. A qualitative research design with a case study method was applied in this research. Interviews and document analysis were conducted to gain in-depth information and understanding on the subject, while thematic analysis was used to analyze and describe the collected data. Triangulation and member checking were used to assess the trustworthiness of the research results. The results indicated that the main problems encountered by the teachers in teaching English to visually-impaired students were associated with time management, students’ attitude and behavior, lack of instructional materials and equipment, and poor classroom condition.